Baseline Peripheral Blood Leukocytosis Is Negatively Correlated With T-Cell Infiltration Predicting Worse Outcome in Colorectal Cancers - Hu, Xiang; Li, Ya-Qi; Li, Qing-Guo; Ma, Yan-Lei; Peng, Jun-Jie; Cai, San-Jun (Frontiers in Immunology, 2018)
We aimed to explore the prognostic value of blood leukocyte and to generate a predictive model to refine risk stratification for colorectal cancers. 6558 patients with colorectal cancers were identified eligible respectively in Fudan University Shanghai Cancer Center (FUSCC) between May, 2008 and October, 2016. Then the entire set is divided into a training set and a testing set. The prognostic value of pretreatment white blood cell count and clinicopathologic parameters in the context of tumor-infiltrating lymphocytes (TIL) and neutrophils was investigated. Conventional leukocytosis (≥10,000/μl) was significantly associated with decreased overall survival (OS) and disease-free survival (DFS) (p < 0.05). In fact, moderately elevated leukocyte (≥7,500/μl) has also been identified as an independent prognostic factor for survivals in the training, testing, and entire sets, respectively. And leukocytosis correlated with advanced T-stage (p<0.001), M-stage (p<0.001), poor differentiation tumor (p=0.023) and Glasgow prognostic score, even predicted for worse relapse postoperatively (p=0.001) and resistance to chemotherapy. In addition, nomograms on OS and DFS were established according to leukocytosis and other significant factors, demonstrating a great prediction accuracy. Importantly, pretreatment leukocytosis had a significantly lower intra-tumor CD3+ and CD8+ TIL infiltration (p< 0.001 and p=0.033), whereas low CD3+ and CD8+ TIL expression in tumor were associated with worse OS and DFS (p=0.02 and p=0.015). In conclusion, our study validates leukocytosis as an independent prognostic factor in colorectal cancers. Our data provide for the first-time vital insight on the correlation of peripheral pretreatment leukocytosis with the tumor-infiltrating cells contexture and might be relevant for future risk stratification.